Dinamika Tradisi Tegal Deso dalam Kerangka Sistem Sosial Budaya Indonesia di Desa Made Kec. Sambikerep Kota Surabaya - Yola Erlanda; Ghulam Maulana Ilman (Jurnal Media Administrasi, 2023)
The sedekah bumi tradition held by the people of Kelurahan Made is a tradition handed down from their ancestors which is still being preserved to this day. Earth almsgiving means giving alms to the earth, which is a form of human gratitude for gifts from the Almighty. The aim of this research is to describe the socio-cultural values in the implementation of the earth alms tradition in Kelurahan Made so that the community continues. The benefit of this research for the community is to increase insight into the importance of preserving traditions passed down from generation to generation so that the community can maintain tolerance between religious groups, tribes and nations. , so that the earth alms tradition can be implemented in the midst of the modernization era without eliminating the characteristics, values and philosophy of the earth alms tradition. This study used descriptive qualitative method. With the aim of producing descriptive data in the form of written sentences, this research contains a description or describes a situation in the problem that has been formulated. The socio-cultural values contained in this earth charity tradition are religious, artistic, mutual cooperation and ecological values. To maintain the unique characteristics of the Kelurahan Made community, it is appropriate to preserve the earth alms tradition forever, even in the midst of changing times. It is intended that traditions that have been passed down through generations can continue to exist and become a cultural identity that will forever be attached to the people of Kelurahan Made.